Highly Electronegative V2CTx/Silicone Nanocomposite‐Based Serpentine Triboelectric Nanogenerator for Wearable Self‐Powered Sensors and Sign Language Interpretation. Issue 10 (25th January 2023) - Salauddin, Md.; Rana, S. M. Sohel; Sharifuzzaman, Md.; Song, Hye Su; Reza, Md. Selim; Jeong, Seong Hoon; Park, Jae Yeong
Abstract: The functionality and use of wearable triboelectric nanogenerators (TENGs) are significantly impacted by the development of their tribomaterial properties. Herein, a novel charge‐generating layer (CGL) composed of a V2 CT x /Silicone nanocomposite and serpentine TENG (S‐TENG) is introduced. The V2 CT x /Silicone nanocomposite exhibits a highly electronegative surface, which significantly enhances the surface potential and charge density. The fabricated nanocomposite‐based TENG exhibits a peak power density of 19.75 W m −2 . It also exhibits a high mechanical stretchability (400%), which is significantly better than those of previously reported TENGs under small external pressure. The optimized S‐TENG is demonstrated as a self‐powered human motion sensor with high sensitivity (4.93 V kPa −1 ) and a quick rise time (21 ms). Furthermore, a real‐life demonstration of sign language interpretation using finger motion detection and text conversion via smartphones is successfully performed. Additionally, the real‐time sensing ability of the S‐TENG is demonstrated in virtual reality car games controlled by finger touch. The S‐TENG is demonstrated to capture different types of human motion energy for continuously powering a stopwatch and wristwatch. Therefore, it is expected that the V2 CT x /Silicone nanocomposite will continue with the contributions of novel CGL materials for various TENG applications including wearable self‐powered sensors, robotics, and healthcare monitoring in IoT platforms. Abstract : A new charge‐generating layer composed of a V2 CT x /silicone nanocomposite and serpentine triboelectric nanogenerator (S‐TENG) is reported. The V2 CT x /silicone nanocomposite exhibits a highly electronegative surface, which significantly enhances the surface potential and charge density. The optimized S‐TENG is demonstrated as a self‐powered human motion sensor with high sensitivity (4.93 V kPa −1 ) and a quick rise time (21 ms).